Pengembangan Dimensi Kemanusiaan dalam Pendidikan Islam - Umami, Ida (Didaktika Religia, 2015)
This paper discusses Islamic education and its relationship with the informationof ideal criteria and the sources of the noble character. The combination of thosetwo things mentioned is an interesting offer. This illustration becomes, at once,an entry point to state that the education character has something to do withthe spirituality values. In the operational context, the morality education is aneffort to equip the students through counselling, instruction, and training duringtheir growth time. Such effort is meant to create human with a clean heart, goodbehaviour, decent worship to God, and well-behaved response to God’s creation.The morality education, in turn, lead to a holistic personality possessing a highmoral standard in speech, action, attitude, thought, feeling, work, and outputwhich are in line with the religious values, norms, and the noble moral of thenation. The character education should be developed within oneself. It is manifestedin a process or an activity aimed at integrating the essential values. Such is basedon the assumption that human is a creature who possesses the capability to learnand give meaning to essential values existing in their life. The very fundamentalthing within the process of character education is the value integration conductedthrough broadening the insight on how to live meaningfullyKey words: Dimension, development, humanity, Islamic education